What it means for people to be mechanically ventilated via a tracheostomy at home: a qualitative study - Nelissen, Veronika; Metzing, Sabine; Schnepp, Wilfried (Central European Journal of Nursing and Midwifery, 2019)
Aim:Some patients with an acute or chronic disease need home mechanical ventilation via a tracheostomy (invasive HMV). Little is known about the experiences of those affected. This study examined the experiences and life circumstances of peopleinGermany with invasive HMV. Design:A qualitative research design was selected. Methods:Problem-centered interviews were held with 20 patients who received invasive HMV. Grounded Theory method and methodology were used. Results:Theaffected people realize that they need invasive HMV and that this will allow them to continue to live. They want to be seen as human beings and to be able to trust the nursing staff. However, they need information and to be able to communicate,thereby regaining their independence and leadinga self-determined life. Conclusion:The participants just want to live their life despite invasive HMV.The knowledge and experience of nurses can inspire trust and give those affected the necessarysense of safety.
Keywords: rozhovory jako téma; dospělí; Qualitative Research; Germany; Interviews as Topic; Female; Tracheostomy; Adult; ženské pohlaví; tracheostomie; lidé; Německo; Male; Aged; lidé středního věku; senioři; mužské pohlaví; Middle Aged; kvalitativní výzkum; Humans